Changes in feeding habits of the starspotted smooth-hound, Mustelus manazo, in Tokyo Bay between periods with different stock size levels. (March 2020) - Park, Jeong-Chae; Kodama, Keita; Oyama, Masaaki; Lee, Jeong-Hoon; Ohta, Yasuhiko; Yamaguchi, Atsuko; Shiraishi, Hiroaki; Horiguchi, Toshihiro
Abstract: We investigated differences in the feeding habits of the starspotted smooth-hound, Mustelus manazo, in Tokyo Bay between the mid-1990s (low stock size) and the late 2000s (high stock size). The frequency of M. manazo with empty stomachs increased from 5.9% in the mid-1990s to 16.1% in the late 2000s. A decrease in the relative weight of the stomach contents was evident from the mid-1990s to the late 2000s, especially in the small size classes, along with changes in the species composition in the stomach contents. Although crustaceans were the main constituents of the stomach contents, the proportion of crabs increased while those of shrimps and hermit crabs decreased. Changes in the feeding habits of M. manazo may be associated with shifts in the benthic community structure in Tokyo Bay. Highlights: Feeding habits of Mustelus manazo in Tokyo Bay changed with their stock size. The rate of M. manazo with empty stomachs increased in the high stock size period. Prey consumption by M. manazo decreased in the high stock size period. Species composition in the stomach contents changed greatly over time. Changes in feeding habit may reflect changes in benthic community structure.